Enantioselective Alkynylation of Trifluoromethyl Ketones Catalyzed by Cation‐Binding Salen Nickel Complexes. (2nd December 2019) - Park, Dongseong; Jette, Carina I.; Kim, Jiyun; Jung, Woo‐Ok; Lee, Yongmin; Park, Jongwoo; Kang, Seungyoon; Han, Min Su; Stoltz, Brian M.; Hong, Sukwon
Abstract: Cation‐binding salen nickel catalysts were developed for the enantioselective alkynylation of trifluoromethyl ketones in high yield (up to 99 %) and high enantioselectivity (up to 97 % ee ). The reaction proceeds with substoichiometric quantities of base (10–20 mol % KO t ‐Bu) and open to air. In the case of trifluoromethyl vinyl ketones, excellent chemo‐selectivity was observed, generating 1, 2‐addition products exclusively over 1, 4‐addition products. UV‐vis analysis revealed the pendant oligo‐ether group of the catalyst strongly binds to the potassium cation (K + ) with 1:1 binding stoichiometry ( K a =6.6×10 5 m −1 ). Abstract : Kationenbindende Salen‐Nickel ‐Katalysatoren wurden für die enantioselektive Alkylierung von Trifluormethylketonen entwickelt. Die Reaktion gelingt mit substöchiometrischen Mengen an Base (10–20 mol % KO t ‐Bu) im offenen Gefäß. Laut UV/Vis‐Analyse bindet die anhängende Oligoethergruppe des Katalysators stark an das Kaliumkation mit 1:1‐Stöchiometrie ( K a =6.6×10 5 m −1 ).